Whole genome sequencing in Mycobacterium tuberculosis - Spitaleri, Andrea; Ghodousi, Arash; Miotto, Paolo; Cirillo, Daniela Maria (Annals of Translational Medicine; Vol 7, Supplement 6 (September 20, 2019): Annals of Translational Medicine, 2019)
Fighting the emergence of multidrug-resistant (MDR) and extensively drug-resistant (XDR) tuberculosis (TB) requires a proper and personalized use of new antitubercular drugs. To achieve this goal, the sensitivity profile to antitubercular drug should be available in a short-time and results should be highly reliable be used for patient-care.